Analysis and Psychoeducational Implications of the Behavior Factor During the COVID-19 Emergency - de la Fuente, Jesús; Kauffman, Douglass F.; Dempsy, Michael S.; Kauffman, Yashu (Frontiers in Psychology, 2021)
This theoretical analysis seeks to contribute to three objectives within the context of the proposed Frontiers Research Topic: (1) Delimit two levels of analysis in the present pandemic situation: medicine-epidemiology, and behavioral psychology, still under-addressed. While medicine has its essential role on the biological side, psychology has a comparable role on the behavioral side. (2) Analyze the importance of behavioral-educational factors in the pandemic situation, using a precise theoretical model from educational psychology for this analysis. (3) Propose preventive, psychoeducational intervention strategies based on the previous analyses.